Science Learning Strategies in Elementary Schools - Ngurah Mahendra Dinatha; Dimas Qondias; Dek Ngurah Laba Laksana; Gervarsia Virjinlia Anita Dhena; Yosefina Owa Meme (International Journal of Instructions and Language Studies, 2023)
Science learning is a process that allows students to gain direct experiences, enabling them to enhance their abilities to comprehend, retain, and apply the concepts they have learned. This research method involves a literature review aimed at discussing science teaching strategies for elementary school students in character development. The criteria for scientific articles used as data consist of scholarly articles sourced from national journals published within the past 5 years, from 2018 to 2023. The study reveals various science teaching strategies that can be adapted by elementary school teachers to match the students' characteristics and learning styles, including: 1) Guided Inquiry, 2) Contextual Teaching and Learning (CTL), 3) Project-Based Learning (PjBL), and Outdoor Learning. Factors influencing students' learning outcomes consist of internal and external factors. Students' learning styles constitute an internal factor, encompassing visual, auditory, kinesthetic, and visual-auditory learning styles. External factors include the students' learning environment